Development of Emission Control Devices for Petrol Engines (Catalytic Convertor) - Balashanmugam, P.; Nath, Sangeeta; Paswan, Sanjay; Kaushal, Gaurav; Verma, Kunal; Prasad, Pankaj Kumar (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
Petrol power inevitably finds a very important role in the development of the plant’s economy and technical growth. Inspite of their high thermal efficiency, one cannot ignore the fact about the effect of their exhaust, in the atmosphere. It is a well-known fact that the toxic gases emitted in petrol engines are less than the engines. Due to high cost of petrol, petrol engines are more in use. Anticipating the use of petrol engines, even more in the near future; this system developed can be used to control the toxic gases, coming out of the petrol engines. These toxic gases are harmful not only to the atmosphere, but also to the human & animal race. Objective of this project is to design & fabricate a simple system, where the toxic levels are controlled through chemical reaction to more agreeable level. This system acts itself as a silencer; there is no need to separate the silencer. The whole assembly is fitted in the exhaust pipe; it does not give rise to any complications in assembling it. This system is Very cost effective and more economical. The automobiles play an important role in the transport system. With an increase in population and living standard, the transport vehicles as well as car population is increasing day by day. In addition to this there is a steep increase in the number of two wheelers during the last two decades. All these are increasing exhaust pollution and particularly in metros as density of these vehicles in metros are very high. The main pollutants contributed by I.C. engines are CO, NOX unburned hydrocarbons (HC) and other particulate emissions. Other sources such as Electric power stations, industrial and domestic fuel consumers also add pollution like NOX, SO2 and particulate matters. In addition to this, all fuel burning systems emit CO2 in large quantities and this is more concerned with the Green House Effect, which is going to decide the health of the earth. Lot of efforts is made to reduce the air pollution from petrol and diesel engines and regulations for emission limits are also imposed in the USA and in a few cities of India. An extensive analysis of energy usage and pollution shows that alternative power systems are still a long way behind the conventional ones. Further developments in petrol and diesel engines, combined with improvements in the vehicles, will make fuel consumption reduction of 40% or more in the future cars. This, in turn, will reduce the CO2 emissions, a gas which is responsible for the greenhouse effect.